Introduction to the Multimedia Semantics issue - Grosky, B.; Stanchev, P.L. (Journal of Digital Information Management, 2006)

Some issues in the art image database systems - Stanchev, P.L.; Green Jr., D.; Dimitrov, B. (Journal of Digital Information Management, 2006)
In this paper we illustrate several aspects of art databases, such as: the spread of the multimedia art images; the main characteristics of art images; main art images search models; unique characteristics for art image retrieval; the importance of the sensory and semantic gaps. In addition, we present several interesting features of an art image database, such as: image indexing; feature extraction; analysis on various levels of precision; style classification. We stress color features and their base, painting analysis and painting styles. We study also which MPEG-7 descriptors are best for fine painting images retrieval. An experimental system is developed to see how these descriptors work on 900 art images from several remarkable art periods. On the base of our experiments some suggestions for improving the process of searching and analysis of fine art images are given.
Keywords: Art databases; Image processing; Image search and analysis; MPEG 7; Multimedia databases